Development of Student Worksheets Based on the SAVI Learning Model for Grade V Elementary School Students - Al Fuad, Zaki; Mardhatillah, Mardhatillah; Musdiani, Musdiani; Helminsyah, Helminsyah; Marlini, Cut; Kasmini, Lili; Subhananto, Aprian; Lestari, Ayuni (Teunuleh Publisher, 2023)
During the learning activities, only teachers are active and still use lectures in the learning process, while students are still less active in engaging in learning activities. Besides, information was obtained that so far teachers only use student worksheets sold in the market, meaning that teachers have never developed worksheets that are suitable for topics and learning models that are suitable for student characteristics. Student worksheets that are sold freely are very general, not yet able to reach the characteristics of students in each region. The formulation of the problem in this study is what is the level of validity of the worksheets based on the SAVI learning model (somatic, auditory, visual, and intellectual) on the knowledge competencies of Grade V students of SD Negeri 19 Banda Aceh? and can worksheets based on the SAVI learning model (somatic, auditory, visual, and intellectual) improve the knowledge competence of grade V students of SD Negeri 19 Banda Aceh ?. The objectives of the study were to determine the validity level of student worksheets based on the SAVI learning model (somatic, auditory, visual, and intellectual) on the knowledge competencies of Class V students at SD Negeri 19 Banda Aceh and to find out whether the worksheets is based on the SAVI learning model (somatic, auditory, visual, and Intellectual) can improve the knowledge competence of fifth-grade students of SD Negeri 19 Banda Aceh. Data collection techniques using tests and checklists. Data analysis uses a scale to see whether the student worksheets are valid or not. As for the test results using statistical tests. The results showed that the worksheets based on the SAVI learning model was feasible to use to improve the knowledge competence of fifth-grade students of SD Negeri 19 Banda Aceh. This is reinforced by the test results which show there are differences in learning outcomes before and after students are taught using worksheets based on the SAVI learning model, where the results of student tests after being taught using worksheets based on the SAVI learning model are better than before.